Aristotle on the voluntariness of self-control and the lack of self-control (EE II 8, 1224a7-1225a2). Issue 1 (2nd January 2021) - Di Basilio, Giulio
ABSTRACT: I argue that in Eudemian Ethics II 8 Aristotle provides us with a general definition of force ( bia ) applicable to all natural phenomena. This definition points us to an important, though rarely noticed, requirement for voluntary action; namely that the impulse acted upon be natural to its possessor. The definition of force is further put to use in the chapter to solve puzzles concerning self-control and the lack of it. In addition to laying bare his solution to these puzzles, I emphasize Aristotle's keen interest in explaining the mistake of his opponents; namely those who deny that self-control and its lack are voluntary. Most importantly, some of Aristotle's replies work with premisses accepted by, and granted to, his interlocutors to point out their mistakes.